Geochemical features of the elemental composition of meadowsweet (Filipendula ulmaria (L).Maxim) in Kemerovo Oblast; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Zhdanov V. A.; Sobolev I. S. Igor Stanislavovich; Baranovskaya N. V. Nataliya Vladimirovna; Kolesnikova E. A.; Chernenkaya E. V.; Yalaltdinova A. R. Albina Rashidovna (Geoecology and Environmental Protection, 2016)
Title screen